2021
DOI: 10.1007/s11120-021-00841-3
|View full text |Cite
|
Sign up to set email alerts
|

Singlet oxygen damages the function of Photosystem II in isolated thylakoids and in the green alga Chlorella sorokiniana

Abstract: Singlet oxygen (1O2) is an important damaging agent, which is produced during illumination by the interaction of the triplet excited state pigment molecules with molecular oxygen. In cells of photosynthetic organisms 1O2 is formed primarily in chlorophyll containing complexes, and damages pigments, lipids, proteins and other cellular constituents in their environment. A useful approach to study the physiological role of 1O2 is the utilization of external photosensitizers. In the present study, we employed a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 87 publications
(137 reference statements)
0
9
0
Order By: Relevance
“…7,8 There are several hypothetical mechanisms proposed associated with photodamage to PSII depending on whether light energy is initially absorbed by the photosynthetic pigment, the Mn cluster, or both. 9,10 Further, the formation of singlet oxygen by the interaction of molecular oxygen with the excited triplet state of chlorophyll has been identified as one of the main causes of the oxidative stress that causes the degradation, 9,11 requiring the PSII to reassemble every 20 to 40 minutes. 12 Assuming that the OEC-PSII turnover is at ms time scale, it makes roughly 1.2–2.4 million turnovers (TONs) before it is replaced.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 There are several hypothetical mechanisms proposed associated with photodamage to PSII depending on whether light energy is initially absorbed by the photosynthetic pigment, the Mn cluster, or both. 9,10 Further, the formation of singlet oxygen by the interaction of molecular oxygen with the excited triplet state of chlorophyll has been identified as one of the main causes of the oxidative stress that causes the degradation, 9,11 requiring the PSII to reassemble every 20 to 40 minutes. 12 Assuming that the OEC-PSII turnover is at ms time scale, it makes roughly 1.2–2.4 million turnovers (TONs) before it is replaced.…”
Section: Introductionmentioning
confidence: 99%
“…It can participate in diverse intracellular processes, damaging macromolecules, oxidizing proteins, fatty acids, and nucleotides (Krieger-Liszkay, 2005)(Di Mascio et al ., 2019; Pospíšil et al ., 2022), inducing adverse effects on cells. One of its most significant physiological effect in the photosynthetic apparatus is the damage of the structure and function of the Photosystem II (PSII) reaction centre under high light exposure (Okada et al ., 1996; Mizusawa et al ., 2003; Krieger-Liszkay, 2005; Krieger-Liszkay et al ., 2008; Rehman et al ., 2013; Bashir et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also on PSI, Oguchi et al (2021) investigated the rate of the photoinhibition in Photosystem I under different wavelengths of visible light and revealed that by varying the wavelengths, the rates of photoinhibition of PSI and PSII are different, and that PSI and PSII are independently photoinhibited with different mechanisms. Bashir et al (2021) show how extrinsic photosensitization of 1 O 2 can contribute during PSII photodamage in thylakoid membranes and green algae. Finally, Zavafer 2021 presents a synthesis of all the literature of the last decade supporting the dual hypothesis of PSII photoinhibition.…”
mentioning
confidence: 96%